The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00466-011-0617-2
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities of the particle finite element method for fluid–soil–structure interaction problems

Abstract: We present some developments in the particle finite element method (PFEM) for analysis of complex coupled problems in mechanics involving fluid-soil-structure interaction (FSSI). The PFEM uses an updated Lagrangian description to model the motion of nodes (particles) in both the fluid and the solid domains (the later including soil/rock and structures). A mesh connects the particles (nodes) defining the discretized domain where the governing equations for each of the constituent materials are solved as in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 151 publications
(103 citation statements)
references
References 42 publications
(74 reference statements)
2
96
0
5
Order By: Relevance
“…(25) and (26) result from the FIC assumptions and, as usual, h ij and h k are the characteristic length parameters. The governing equations are completed with the adequate boundary conditions.…”
Section: A Particle Finite Element Methods Via Ficmentioning
confidence: 99%
“…(25) and (26) result from the FIC assumptions and, as usual, h ij and h k are the characteristic length parameters. The governing equations are completed with the adequate boundary conditions.…”
Section: A Particle Finite Element Methods Via Ficmentioning
confidence: 99%
“…The coupling effects between the particles and the fluid are introduced via an immersed technique [3][4][5]. The fluid motion is modelled either with an Eulerian stabilized FEM formulation using a fixed mesh, or using a Lagrangian formulation using the Particle Finite Element Method (PFEM) [4,[6][7][8][9][10][11][12][13][14][15][16] for which the mesh evolves in time. For both the Eulerian and the Lagrangian formulations we use a mixed finite element formulation with an equal order linear interpolation for the velocities and the pressure variables.…”
Section: Introductionmentioning
confidence: 99%
“…Another source of instability, however, remains in the numerical solution of Lagrangian flows such as PFEM, that due to the treatment of the incompressibility constraint which still requires using a stabilized numerical method. In this work we use a PFEM formulation based on a residual-based stabilized expression of the mass balance equation [10][11][12][13][14][15][16]. The excellent mass preservation feature of this formulation has been demonstrated previously [7,16].…”
Section: Introductionmentioning
confidence: 99%
“…The PFEM has also been tested successfully in other kind of problems, such as fluid mechanics including thermal convection-diffusion [5,80,95], multi-fluids [36,62], granular materials [131], bed erosion [87], FSI [81,132] and excavation [19].…”
Section: Eulerian and Lagrangian Approaches For Free Surface Flow Anamentioning
confidence: 99%
“…In previous works it has been found that the computational time associated to the remeshing grows linearly with the number of nodes [81]. Specifically, for a single processor Pentium IV PC the meshing consumes for 3D problems around 15% of the total CPU time per time step, while the solution of the equations (with typically 3 iterations per time step) and the consists on leaving the wall particles move along the direction of the wall until when the separation from the original position is larger than a prearranged critical distance.…”
Section: Advantages and Disadvantagesmentioning
confidence: 99%